Etnička sekularizacija ustavnog prava / Ethic Secularization of Constitutional Law: Standard pluralističkog društva / Standard for Pluralistic Society - Gotovuša, Ena (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
By analyzing the European Court of Human Rights rulings against Bosnia and Herzegovina, the author provides a detailed explanation of the characteristics of the Constitution of Bosnia and Herzegovina and the necessity to change it in order to harmonize it with provisions of the European Convention for the Protection of Human Rights and Fundamental Freedoms. Need for ethnic secularization of constitutional law of Bosnia and Herzegovina, before the European Court of Human Rights rulings were made, was indicated by academician Edin Šarčević. Contemplating arguments of European Court of Human Rights and academician Edin Šarčević, the author came to the unambiguous conclusion that Bosnia and Herzegovina can become a full member state of the European Union only if abstract citizen has primacy in constitutional provisions over a member of constituent peoples. This does not in any way preclude protection of the collective rights of the ethnic groups – constituent peoples. However, analysis of real-political relations shows a principle of „hopelessness“: promoting the European path for Bosnia and Herzegovina, not enforcing the European Court of Human Rights rulings and maintaining status quo.